2005
DOI: 10.1111/j.1600-0714.2004.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

HCV clearance patterns in saliva and serum of patients with chronic HCV infection under interferon plus ribavirin therapy

Abstract: The present results suggest that the monitoring of salivary levels of HCV would be a helpful means of determining sustained antiviral effects of interferon and ribavirin in the treatment of HCV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In a previous study of patients with chronic hepatitis C monoinfection, (Diz Dios et al , ) defined three patterns of HCV clearance from the saliva with respect to the serum response to treatment with PEG‐IFN‐RIB: Pattern 1 or ‘concordant clearance’ of HCV from the blood and saliva; Pattern 2 or ‘delayed clearance’; and Pattern 3 or ‘discordant clearance’. Applying these criteria, at 24 weeks post‐treatment, we found a clear predominance of pattern 1, which was observed in 22 patients (the virus was undetectable in both fluids in 11 patients and was present in both fluids in the other 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of patients with chronic hepatitis C monoinfection, (Diz Dios et al , ) defined three patterns of HCV clearance from the saliva with respect to the serum response to treatment with PEG‐IFN‐RIB: Pattern 1 or ‘concordant clearance’ of HCV from the blood and saliva; Pattern 2 or ‘delayed clearance’; and Pattern 3 or ‘discordant clearance’. Applying these criteria, at 24 weeks post‐treatment, we found a clear predominance of pattern 1, which was observed in 22 patients (the virus was undetectable in both fluids in 11 patients and was present in both fluids in the other 11).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have considered whether the rate of HCV detection in saliva could be related to the HCV serum viral load in patients with HCV monoinfection (Mariette et al., ; Hermida et al., ). The administration of pegylated interferon plus ribavirin (PEG‐IFN‐RIB) leads to a significant reduction in viraemia, and it has been suggested that HCV‐RNA analysis on the saliva could be useful to monitor maintenance of the antiviral effect of this therapeutic combination (Diz Dios et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also greatly need better estimates of global HCV costs including oral healthcare needs that continue to be concerning overlooked (Carrozzo, 2001), particularly if comparing to the amount of information available for HIV (Vernon et al, 2014). Preliminary data suggested that HCV-RNA analysis on the saliva could be useful to monitor antiviral treatment (Diz Dios et al, 2005;Feijoo et al, 2014), and further studies are clearly warranted.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In the study, paired serum and saliva specimens were collected and analyzed by nested-PCR from 44 chronic HCV-infected patients at baseline, 4 and 12 weeks after start, at the end and 6 months after treatment. Their findings showed that saliva had the capability of monitoring HCV RNA levels as a means of determining sustained antiviral response to interferon and ribavirin treatment (97).…”
Section: Hepatitis C Virusmentioning
confidence: 99%